Pengaruh Tepung Umbi Garut (Maranta aryndinacea) terhadap Kandungan Gizi dan Sifat Organoleptik Mi Kering - Zhafira, Andrea Siti; Farida, Eko (Indonesian Journal of Public Health and Nutrition, 2023)
Background: Noodles are one of the foods that are popular with the community as an alternative to staple foods. The need for flour, which is the basic ingredient for making noodles is obtained by importing in large quantities, this makes imports of wheat in Indonesia increase. This study aims to obtain the best formulation of dry noodles with the addition of arrowroot flour as an alternative to reduce dependence on wheat flour in terms of nutritional content, dietary fiber content, and organoleptic properties. Methods: This type of research was experimental with a completely randomized design (CRD). The ratio of arrowroot flour and wheat flour in the three formulations was 21,81%:50,90% (T1); 29,09%:43,64% (T2); and 36,36%:36,36% (T3). Nutrient content and dietary fiber data were analyzed by One Way Anova test with a 95% confidence level and then tested by the Duncan test. Organoleptic properties data were analyzed by Kruskal-Wallis test followed by the Mann Whitney test. The best dry noodle formulation was determined by the de Garmo effectiveness index. Result: The results of the energy content of T1 403,63 kcal, T2 386,08 kcal, T3 390,02 kcal, protein T1 7,40%, T2 9.37%, T3 8,39%, T1 fat 11.57%, T2 8, 98%, T3 11.32%, carbohydrates T1 67.47%, T2 66.93%, T3 63,70%, ash content T1 2,82%, T2 2,75%, T3 3,38%, water content T1 10,73%, T2 11,95%, T3 13,19%, and dietary fiber T1 7,44%, T2 8,39%, T3 8,14%. The test results of the preferred organoleptic properties on the color and texture of T2, the aroma of T3, the taste of T1. Conclusion: There are differences in water content, dietary fiber, color, taste, and texture in the three formulations of dry noodles with the addition of arrowroot flour.